A New Clinical Section in PLoS Neglected Tropical Diseases - Carlos Franco‐Paredes; Albert I. Ko; Serap Aksoy; Peter J. Hotez (2010)
PLoS Neglected Tropical Diseases (PLoS NTDs) provides a platform of information that links multiple scientific disciplines in the battle against the substantial public health and economic impact imposed by neglected tropical diseases (NTDs). The types of articles published in PLoS NTDs include health policy; control, elimination, and eradication programs; epidemiological and operational research; basic pathobiology, translational research, and development; development of new diagnostic tests; and many other areas of action.